Anti-Theft Box: Arduino Safety Box with IoT Notifications - Muzaffar Alfian, Mohamad Norul Hafiz; Mas Erwan, Athirah Nabihah; Mohamad Adenan, Mohamad Syafiq (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Theft cases often go unnoticed and are everywhere we are. It can happen in public, at school, at work or even in your own home. Things like this often happen to teens and older adults. Some of them do not have a safe place to store their valuables because of their carelessness. This is because they do not take this seriously. On the other hand, they already have their own safety box which is a great example of keeping items from being stolen or robbed. With the Internet of Things (IoT), this safety box can be improved by adding features that make it even safer to receive notifications on a mobile phone when the safety box is opened. With these improvements, property owners will become more aware of their goods because not everyone around us can be trusted. The use of these notifications is an update that will be created to improve the security of your goods. The methodology used to carry out this project is called Prototyping Method. In this way, prototype can be said to be both a design and an example of an existing system, but not yet fully functional. Prototypes will outline how a system works, and most prototype systems are not yet the perfect system to run.